Finding Order in the Chaos: Outstanding Questions in Klebsiella pneumoniae Pathogenesis - Gonzalez-Ferrer, Shekina; Peñaloza, Hernán F; Budnick, James A; Bain, William G; Nordstrom, Hayley R; Lee, Janet S; Van Tyne, Daria (Infection and immunity, 2021)
are Gram-negative facultative anaerobes that are found within host-associated commensal microbiomes, but they can also cause a wide range of infections that are often difficult to treat. These infections are caused by different pathotypes of , called either classical or hypervirulent strains. These two groups are genetically distinct, inhabit nonoverlapping geographies, and cause different types of harmful infections in humans. These distinct bacterial groups have also been found to interact differently with the host immune system. Initial innate immune defenses against infection include complement, macrophages, neutrophils, and monocytes; these defenses are primary strategies employed by the host to clear infections. pathogenesis depends upon the interactions between the microbe and each of these host defenses, and it is becoming increasingly apparent that bacterial genetic diversity impacts the outcomes of these interactions. Here, we highlight recent advances in our understanding of pathogenesis, with a focus on how bacterial evolution and diversity impact interactions with mammalian innate immune host defenses. We also discuss outstanding questions regarding how can frustrate normal immune responses, capitalize upon states of immunocompromise, and cause infections with high mortality.